Zambia : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This paper analyzes the efforts taken to create fiscal space for the implementation of the fifth national development plan and the risk associated with it, examines the role of monetary policy in determining inflation, and discusses policy options to achieve low inflation. It also identifies areas where reform strategy needs more attention and suggests that reforms of financial system regulation need to be accelerated to ensure stability of the system. It analyzes traditional reserve adequacy measures, and finds looming power crisis as an obstacle to growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet